PENYULUHAN GANGGUAN PENDENGARAN PADA REMAJA SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT DI SEKOLAH MENENGAH ATAS NEGERI 3 SINGARAJA - BALI - Ida Ayu Mirah Agung,; Ni Ketut Lyra Sakhya Melani,; Anak Agung Sagung Candra Mahesuari,; Ida Ayu Puspa Juwita Manuaba, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
With the increasing use of personal listening devices (PLDs) such as headsets and true wireless stereo (TWS) for digital music devices, constant exposure to loud noise has become a serious threat to the hearing health of the younger generation. While the use of headsets or TWS has become an integral part of teenagers' daily lives, it turns out to pose serious risks to hearing health. The material presented covered important topics, including: safe volume limits (not more than 85 dB), recommended listening duration (the 60/60 rule—listen at no more than 60% volume for 60 minutes, then take a break), and the importance of using noise-canceling headsets or TWS to reduce the need to increase the volume. The education also emphasized that early symptoms such as tinnitus (ringing in the ears) should not be ignored, as they can be an early indication of permanent damage to the hair cells in the cochlea.